Maqasid Shariah in Family Institutions: Analysis of the Prenuptial Course Module in Malaysia (Mazahib, 2020)
Of significant purposes of marriage in Islam are building self-serenity, developing a harmonious family with positive values, being a perfect platform to show love, affection, and gratitude among each member. Ironically, these purposes are immaterialized in some marriages as divorce cases are still high in Malaysia. Introducing compulsory pre-marriage course is among other actions taken by the government to protect its continuity. This article aims to study the module of the compulsory pre-marriage course and highlights elements of Maqasid Shariah in family and marriage. By Using the descriptive analysis method, this article argues that the modules have covered the whole elements of Maqasid Shariah. For instance, the faith and worship chapter is one factor in maintaining one's marriage and creating an individual's excellent character, which served them a better and happy life while preserving the religion itself. Highlighting Maqasid Shariah elements helps us understand the importance of building a fine family and preserving harmony within. Hence, a candidate who attends this prenuptial course build a good understanding among family members better than those who did not attend the pre-marriage course and, therefore, can maintain their relationship in marriage. Keywords: Maqasid Shariah, prenuptial course module (MKPPI), family institution, Malaysia